2020
DOI: 10.1038/s41586-020-2128-9
|View full text |Cite
|
Sign up to set email alerts
|

The fate of carbon in a mature forest under carbon dioxide enrichment

Abstract: Atmospheric carbon dioxide enrichment (eCO 2) can enhance plant carbon uptake and growth 1,2,3,4,5 , thereby providing an important negative feedback to climate change by slowing the rate of increase of the atmospheric CO 2 concentration 6. While evidence gathered from young aggrading forests has generally indicated a strong CO 2 fertilization effect on biomass growth 3,4,5 , it is unclear whether mature forests respond to eCO 2 in a similar way. In mature trees and forest stands 7,8,9,10 , photosynthetic upta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
217
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(233 citation statements)
references
References 79 publications
14
217
2
Order By: Relevance
“…Reduced rates of mortality due to elevated atmospheric CO 2 concentration (H6b) are conceptually included in five of the TBMs through the growth efficiency concept (Table 3) and are evident in the overall response for two of them (Table 5). Increased plant production under elevated CO 2 follows wellestablished leaf-level responses of photosynthesis and wateruse efficiency to atmospheric CO 2 concentration and is supported by detailed stand-level modelling (Liu et al, 2017), but is hard to verify with observations in mature trees (Jiang et al, 2020;Walker et al, 2019). If trees expend their extra NPP on growing proportionally larger, thereby increasing their respiration demands, then the positive effect of enhanced NPP could be offset.…”
Section: Impact Of Elevated Atmospheric Co 2 Concentration On Mortalimentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced rates of mortality due to elevated atmospheric CO 2 concentration (H6b) are conceptually included in five of the TBMs through the growth efficiency concept (Table 3) and are evident in the overall response for two of them (Table 5). Increased plant production under elevated CO 2 follows wellestablished leaf-level responses of photosynthesis and wateruse efficiency to atmospheric CO 2 concentration and is supported by detailed stand-level modelling (Liu et al, 2017), but is hard to verify with observations in mature trees (Jiang et al, 2020;Walker et al, 2019). If trees expend their extra NPP on growing proportionally larger, thereby increasing their respiration demands, then the positive effect of enhanced NPP could be offset.…”
Section: Impact Of Elevated Atmospheric Co 2 Concentration On Mortalimentioning
confidence: 99%
“…Recently, however, a number of studies have found τ to have comparable or even larger importance than NPP when assessing the response of C veg to environmental change using terrestrial biosphere models (TBMs; Ahlström et al, 2015a;Friend et al, 2014;Galbraith et al, 2013;Johnson et al, 2016;Thurner et al, 2017), with large divergence in TBM projections of τ over the 21st century depending on forcing (Ahlström et al, 2015a) or the choice of TBM (Friend et al, 2014). The divergence that can be traced to TBM structure and parameterisation (Nishina et al, 2015) has not been closely analysed in terms of the contributions of specific underlying processes, interactions and driver dependencies, or their basis in knowledge from real-world ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tools for scrutinizing such changes remain imprecise. On page 252, Ouyang et al 2 report the development of a computational platform that uses an artificial-intelligence (AI) approach to assess cardiac ultrasound video and to provide continuous, beat-by-beat measurement of cardiac pump function.…”
Section: Yiqi Luo and Shuli Niumentioning
confidence: 99%
“…A small number of enrichment experiments have been conducted in young forests, but there is a paucity of knowledge about the CO 2 -fertilization effect in mature forests. On page 227, Jiang et al 2 present results of the Free-Air CO 2 Enrichment (FACE) experiment in a mature forest in Australia. Their estimate of the CO 2 -fertilization effect is among the lowest yet reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation